Peran Hakim Pengadilan Agama dalam Upaya Mengatasi Tingkat Perceraian di Kota Ternate - Suwarti Suwarti (Faculty of Law, Khairun University, 2018)
Divorce is something that must be avoided, because divorce is lawful in its legal position, but the impact it has is quite large both on husband, wife and also his children and on the surrounding community. Islam views divorce as a lawful but very wrath of God, so that divorce is the last resort that can be taken if the household conditions can no longer be maintained, or if the marriage is maintained can lead to greater harm. Therefore Islam considers divorce to be complicated and is the last resort that can be taken by husband and wife if it does not find a solution to the problems of the household. The number of divorces that occurred in the city of Ternate increased partly because of the settlement factor that almost all cases filed ended in litigation at the Ternate City Religious Court, although non-litigation divorce settlement could be taken to reduce the number of divorces submitted